The Impact Of Body Mass Index On Inpatient- Versus Outpatient-Treated Chronic Obstructive Pulmonary Disease Exacerbations - Ariane Jacob; Catherine Laurin; Kim L Lavoie; Gregory Moullec; Maxine Boudreau; Catherine Lemière; Simon L Bacon (Canadian Respiratory Journal)
BACKGROUND: Increased body weight has been associated with worse prognoses for many chronic diseases; however, this relationship is less clear in patients with chronic obstructive pulmonary disease (COPD), with underweight patients experiencing higher morbidity than normal or overweight patients.